Intentions to Consume Sustainable Fashion Products in Indonesia: Does Religiosity Affect ? - Mohamad Soleh Nurzaman; Elvira Herdiani (Faculty of Economic and Business, 2023)
Religiosity is expected to be a positive driving factor of consumption demand for environmentally friendly fashion products. However, few studies have been found that focus on consumer behavior in purchasing sustainable fashion, and none use religiosity as an explanatory variable. This study, therefore, is the first to analyze the effect of religiosity on the intention to consume sustainable fashion products. This study used a quantitative approach with the Structural Equation Modelling (SEM) analysis method and involved 522 respondents in Indonesia. By adopting the theory of planned behavior model, the study results show that religiosity significantly positively affects purchase intentions of sustainable fashion products through the variables' attitude towards behavior and perceived behavioral control. At the same time, the green thinking variable also has a positive impact, but altruism is irrelevant to sustainable fashion consumption. These results indicate that if the consumer is religious, this can lead to a better environmentally friendly attitude and result in a tendency to consume sustainable fashion products.JEL Classification: D12, D90, Z12How to Cite:Nurzaman, M. S., & Herdiani, E. (2023). Intentions to Consume Sustainable Fashion Products in Indonesia: Does Religiosity Affect? Etikonomi, 22(2), 277 – 292. https://doi.org/10.15408/etk.v22i2.34281.